2022
DOI: 10.1111/pbi.13838
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide analyses of PAM‐relaxed Cas9 genome editors reveal substantial off‐target effects by ABE8e in rice

Abstract: PAM-relaxed Cas9 nucleases, cytosine base editors and adenine base editors are promising tools for precise genome editing in plants. However, their genome-wide off-target effects are largely unexplored. Here, we conduct whole-genome sequencing (WGS) analyses of transgenic plants edited by xCas9, Cas9-NGv1, Cas9-NG, SpRY, nCas9-NG-PmCDA1, nSpRY-PmCDA1 and nSpRY-ABE8e in rice. Our results reveal that Cas9 nuclease and base editors, when coupled with the same guide RNA (gRNA), prefer distinct gRNA-dependent off-t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
28
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 73 publications
5
28
0
Order By: Relevance
“…The results showed that the efficiency and stability of the CRISPR‐Cas12a system were higher than that of the CRISPR‐Cas9 system. This was consistent with previous reports (Tang et al., 2017; Wu et al., 2022). We performed genotype analysis on partial mutants, and the results showed that although Cas9 system also had large fragment deletions, most of the mutations of Cas9 system were 1–3 bp InDel (insertions and deletions), especially 1 bp InDel.…”
Section: Resultssupporting
confidence: 94%
“…The results showed that the efficiency and stability of the CRISPR‐Cas12a system were higher than that of the CRISPR‐Cas9 system. This was consistent with previous reports (Tang et al., 2017; Wu et al., 2022). We performed genotype analysis on partial mutants, and the results showed that although Cas9 system also had large fragment deletions, most of the mutations of Cas9 system were 1–3 bp InDel (insertions and deletions), especially 1 bp InDel.…”
Section: Resultssupporting
confidence: 94%
“…S2 ). Surprisingly, PmCDA1-derived NG-CBE showed no self-editing for both the tested sites similar to a recent report in plants ( 32 ). These results indicated that regardless of self-editing, nCas9-NG-based BEs enable base editing in E. coli .…”
Section: Resultssupporting
confidence: 90%
“…In the case of the PmCDA1-based CBE-NG tool, we did not observe self-editing in bacteria which is consistent with the previous reports of PmCDA1-based CBEs with nCas9 ( 40 ), Cas9-NG, and SpRY ( 32 ) in plant systems. Hence, when desirable, we propose PmCDA1 as a first-choice CBE with PAM-relaxed Cas9 variants.…”
Section: Discussionsupporting
confidence: 92%
“…The results suggest that the mutation type may not be a decisive factor for determining the augmented seed oleic acid content. Although genome editing with the CRISPR/Cas9 system is an efficient method in crop trait improvement, the system has a risk of off-target resulting undesirable mutations because of the similar sequences between on-target and off-target sites ( Park et al., 2022 ; Wu et al., 2022 ). Many strategies were attempted to reduce genome-wide off-target events and made great achievements ( Fu et al., 2014 ; Kleinstiver et al., 2016 ; Zhang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%